Can Complementary Prime-Boost Immunization Strategies Be an Alternative and Promising Vaccine Approach Against Dengue Virus? - Valdés, Iris; Lazo, Laura; Hermida, Lisset; Guillén, Gerardo; Gil, Lázaro (Frontiers in Immunology, 2019)
Dengue is one of the most important diseases transmitted by mosquitoes. Dengvaxia®, a vaccine registered in several countries, cannot be administered to non-immune individuals and children younger than 9 years old, due to safety reasons. There are two vaccine candidates in phase 3 efficacy trials, but their registration date is completely unknown at this moment. So, the development of new vaccines or vaccine strategies continues to be a priority for the WHO. This work reviews some complementary prime-boost immunization studies against important human pathogens. Additionally, it reviews the results obtained using this regimen of immunization against dengue virus as a potential alternative approach for finding a safe and efficient vaccine. Finally, the main elements associated with this strategy are also discussed. The generation of new strategies of vaccination against dengue virus, must be directed to reduce the risk of increasing viral load through sub-neutralizing antibodies and it must be also directed to induce a polyfunctional T cell response. Complementary prime-boost immunization strategies could emerge as an interesting approach to induce solid immunity or at least to reduce viral load after natural infection, avoiding severe dengue. Subunit vaccine could be safe and attractive antigens for this strategy, especially proteins including B, and T-cells epitopes for inducing humoral and cellular immune responses, which can play an important role controlling the disease.